(untitled) (ModaPalavra e-periódico, 2012)
The years 1950 ended for revolutionizing a lot of facets of the society. One of them was the woman’s ideal. With analysis of the section Speaking about Purchases, of the magazine Selections, this article has as objective discusses the changes generated by the economical boom of the decade of 1950 and as that it modified the ideal of the feminine: with the development of products, the daily of the domestic service became faster and comfortable, allowing the woman a rest ideal, happiness and consumption, without neglecting the family needs.